SACRED COWS: THE MYTHS IN THE ENVIRONMENTAL MILITANTS’ SPEECHES - Fábio Angeoletto; Natália da Silva Martins (Travessias, 2010)
In this paper, we analyze five myths usually current in the speeches of environmentalists: the blank slate myth, the myth of cities as the antithesis of nature, the myth of environmental education as a panacea to environmental problems, and the myth of fragility of nature. We have tried to demonstrate that, despite support consensual and politically correct ideas, these myths engender a simplistic view of nature, which does not contribute to solve our ecological dilemmas.